Understanding sentiment toward racial unrest through temporal and geographic lenses: a multilevel-analysis across metropolitan areas in the United States - Lee, Sanguk; Cho, Myung Sik; Peng, Tai-Quan (Frontiers in Communication, 2024)
Racial unrest has long been a salient social issue in the United States. Time and space provide essential contexts for the emergence and evolution of racial unrest. However, the relationships between these contextual factors and public responses to racial unrest remain insufficiently explored. This study seeks to fill that gap, blending geocoded, time-stamped racial unrest tweet data with census information. It aims to explore how temporal elements and geographical characteristics of metropolitan areas contribute to the emergence of negative sentiment reactions to racial unrest on social media platforms. The racially charged unrest that transpired in Ferguson, Missouri in 2014 serves as our case study. We select thirty-three metropolitan regions across the U.S. for our analysis. Our findings indicate that temporal processes, encompassing circadian rhythms, weekday-weekend variations, and temporal decay, correlate with expressions of anxiety and anger, albeit not sadness. Furthermore, our analysis reveals geographical characteristics – notably income inequality and segregation, combined with the number of Black victims – to be associated with manifestations of anxiety.